The impact of corporate social responsibility on the performance of small and medium-sized enterprises can be mediated by innovation ability and learning orientation - Handayati, Puji; Hermawan, Agus; Rochayatun, Sulis; Ratnawati; Nastiti, Ratna Dwi; Palil, Mohd Rizal (International Journal of Management and Sustainability, 2023)
Every company will face complexity, change, and increasingly fierce business competition that occurs not only in large companies but also in Micro, Small, and Medium Enterprises (MSMEs). Achieving competitive advantage for MSMEs requires assistance and guidance from external parties, both government and private, through the Corporate Social Responsibility (CSR) program. This study examines the effect of CSR programs on the innovation ability, learning orientation, and performance of MSMEs. The ability of Innovation and learning orientation to mediate the relationship between CSR programs and the performance of MSMEs. This study’s population is the MSME owners receiving CSR program assistance from the government (BUMN) and the private sector in Tulungagung, Blitar, Malang, Batu, and Sidoarjo districts, with a research sample of 165 MSME owners. Based on Structural Equation Modeling (SEM), the study results show that companies or governments that provide CSR program assistance to SMEs contribute to increasing innovation capabilities. For companies or governments, it is necessary to have a model of CSR assistance. Assistance is related to providing training on how to improve product quality, providing understanding on compliance with legal standards in business management, providing understanding on the formation of a comprehensive code of ethics in business management, and providing understanding about the contribution of SMEs to charity. MSME owners are expected to maximize innovation by adopting new products and developing new product variations. In addition, SME owners need to find solutions to improve the production process and start adopting other MSME production processes to be better than their competitors.